Investigation of the Genotoxic, Cytotoxic, Apoptotic, and Oxidant Effects of Olive Leaf Extracts on Liver Cancer Cell Lines - Bektay, Muhammed Yunus; Guler, Eray Metin; BEKTAY, MUHAMMED YUNUS; Gökçe, Mustafa; GÖKÇE, MUSTAFA; Kızıltaş, Mustafa Volkan (My University, 2021)
Objectives: Hepatocellular carcinoma (HCC) is the seventh most common cancer and the third leading cause of tumor-related deaths worldwide. Mechanisms underlying tumor onset, progression, and metastasis in the case of HCC have not been adequately studied. In this study, we aimed to investigate the genotoxic, cytotoxic, apoptotic and oxidant effects of olive leaf extract (OLE) on HCC cells. Materials and methods: H4IIE Rattus norvegicus hepatoma cells and Rattus norvegicus healthy liver clone-9 cells were treated with the increasing concentrations of OLEs (250-2000 ppm) in ethanol, acetone, dichloromethane, and methanol. ATP cell viability, intracellular reactive oxygen species generation levels, double staining test with acridine orange/ethidium bromide, comet assay, levels of interleukin 1-beta (IL-1β), IL-6, and tumor necrosis factor alpha were measured. Significance was determined using ANOVA test. Results: Apoptotic, genotoxic, cytotoxic, and oxidative effects of OLEs increased with the increasing concentrations as compared to controls in H4IIE cells (p<0.001). Conclusion: This is the first study to show a significant and selective cytotoxic activity of OLEs in the selected H4IIE cancer cell lines. OLEs could selectively increase the apoptotic damage and show anti-proliferative and pro-apoptotic properties against the H4IIE cells. They could be recommended as potential nutraceuticals in the prevention of cancer.
Keywords: Olive leaf; apoptosis; genotoxicity; hepatocellular carcinoma; oleuropein; oxidative stress